Centro de desarrollo infantil incluyente - Obando Román, Alejandro Emilio (Universidad de La Salle. Facultad de Ciencias del Hábitat. Arquitectura., 2017)
In 2012 intersectoral commission for early childhood care " de Cero a Siempre " created the CDC ( Child Development Center ) which aims to unify actions between ICBF and MEN to serve children ages 0 to 6 years, giving priority to the admission of children with disabilities especially children at risk by their poverty that according to the District Diagnosis of Childhood and Adolescence 2011 are 166,145 of the 714,721 children under 5 years living in the urban area of Bogotá , mainly in the towns of Bosa, Kennedy and Ciudad Bolívar , the latter with almost thirty thousand poor children. According to it, of all children in the district about 49% have no access to education because of the high initial qualitative and quantitative deficit in the provision of this service. In this paper an architectural project based on major theories of urban development, psychology and education poses a CDI with a preferably integrative educational approach for children with visual, hearing, motor and cognitive disabilities in Ciudad Bolivar shown.